Down-regulation of S100P induces apoptosis in endometrial epithelial cell during GnRH antagonist protocol - Dan Zhang; Mi Han; Mingjuan Zhou; Mengyu Liu; Yan Li; Bufang Xu; Aijun Zhang (BMC, 2021)
Abstract Background The gonadotropin-releasing hormone (GnRH) antagonist protocol for in vitro fertilization (IVF) often leads to lower pregnancy rates compared to the GnRH agonist protocol. Decreased endometrial receptivity is one reason for the lower success rate, but the mechanisms underlying this phenomenon remain poorly understood. The S100 calcium protein P (S100P) is a biomarker for endometrial receptivity. Both GnRH antagonist and S100P are involved in mediating cell apoptosis. However, the involvement of S100P in reduced endometrial receptivity during the GnRH antagonist protocol remains unclear. Methods Endometrial tissue was collected at the time of implantation window from patients undergoing the GnRH agonist (GnRH-a) or GnRH antagonist (GnRH-ant) protocols, as well as from patients on their natural cycles. Endometrial cell apoptosis and expression levels of S100P, HOXA10, Bax, and Bcl-2 were assessed. Ishikawa cells were cultured to evaluate the effects that GnRH antagonist exposure or S100P up- or down- regulation had on apoptosis. Results Endometrial tissue from patients in the GnRH-ant group showed elevated apoptosis and decreased expression of the anti-apoptotic marker Bcl-2. In addition, endometrial expression of S100P was significantly reduced in the GnRH-ant group, and expression of HOXA10 was lower. Immunofluorescence colocalization analysis revealed that S100P was mainly distributed in the epithelium. In vitro experiments showed that knockdown of S100P in Ishikawa cells induced apoptosis, decreased expression of Bcl-2, while overexpression of S100P caused the opposite effects and decreased expression of Bax. Furthermore, endometrial epithelial cells exposed to GnRH antagonist expressed lower levels of S100P and Bcl-2, increased expression of Bax, and had higher rates of apoptosis. The increased apoptosis induced by GnRH antagonist treatment could be rescued by overexpression of S100P. Conclusions We found that GnRH antagonist treatment induced endometrial epithelial cell apoptosis by down-regulating S100P, which was detrimental to endometrial receptivity. These results further define a mechanistic role for S100P in contributing to endometrial apoptosis during GnRH antagonist treatment, and suggest that S100P is a potential clinical target to improve the success of IVF using the GnRH antagonist protocol.